Analysis of Value Alignment and Ethical Guardianship of Learning with AI in Civic Education - Agustin, Ririn Dwi; Wiyono, Subelo; Yamanto, Redi (Universitas PGRI Kanjuruhan Malang, 2024)
The rapid development of information technology, particularly Artificial Intelligence (AI), has significantly impacted various aspects of human life, including education. This study analyses the value alignment and ethical guardianship of AI-powered learning, specifically ChatGPT, in Civic Education. The research aims to assess how AI, particularly ChatGPT, aligns with moral judgments grounded in Pancasila values, a core component of Civic Education in Indonesia. Using a qualitative approach involving document analysis and expert interviews, this study investigates the ethical implications, potential risks, and safety concerns associated with using ChatGPT in educational settings. The findings indicate that while ChatGPT is user-friendly and capable of processing natural language, there are notable issues related to its accuracy, contextual understanding, and ethical considerations. The study concludes that the responsibility for misinformation or ethical breaches remains ambiguous, necessitating a more cautious approach to integrating AI in Civic Education. The implications suggest the need for comprehensive guidelines and frameworks to ensure that AI tools are used responsibly, maintaining alignment with the cultural and moral values of Indonesia.